Early onset food protein-induced enterocolitis syndrome in two breastfed newborns masquerading as surgical diseases: case reports and literature review. (1st February 2021) - Bosa, Luca; Martelossi, Stefano; Tardini, Giacomo; Midrio, Paola; Lago, Paola
Abstract: Background: Food protein-induced enterocolitis syndrome (FPIES) is a non-immunoglobulin E cell-mediated gastrointestinal food allergy that primarily presents in infancy, as early as the first hours of life. FPIES is often misdiagnosed as sepsis, severe gastroenteritis, abdominal surgical emergency or even metabolic, neurologic, or cardiac disorders. Methods: We report two neonatal cases of cow's milk protein (CMP)-induced FPIES masquerading as surgical diseases. Our purpose is to highlight the diagnostic difficulties in FPIES in this age group and to provide further evidence of the important role played by the prenatal environment in the development of allergic diseases. Results: Case 1 is a 2-day-old boy born at 35th + 5 weeks of gestation admitted to our Neonatal Intensive Care Unit (NICU) for bloody diarrhea who started presenting apnea, crying, pallor, jaundice, and abdominal tenderness. Case 2 is a 3-day-old boy born at 38th +5 weeks of gestation admitted to our NICU for repeated bilious vomiting. Both patients were administered infant formula in the first hours of life, thereafter they received only breast milk. In both cases, CMP allergy was finally suspected and an extensively hydrolyzed formula was administered with the resolution of symptoms. A diagnosis of CMP-induced FPIES was made. Conclusions: FPIES is a heterogeneous disorder. Severe forms of FPIES could be mistaken for surgical diseases, such as necrotizing enterocolitis. A trial of food elimination should be considered whenever diagnostic tests are inconclusive. FPIES must be suspected even in breastfed infants.